Specification of neural cell fate and regulation of neural stem cell proliferation by microRNAs - Pham, Jacqueline T (e-Century Publishing Corporation, 2012)
In the approximately 20 years since microRNAs (miRNAs) were first characterized, they have been shown to play important roles in diverse physiologic functions, particularly those requiring coordinated changes in networks of signaling pathways. The ability of miRNAs to silence expression of multiple gene targets hints at complex connections that research has only begun to elucidate. The nervous system, particularly the brain, and its progenitor cells offer opportunities to examine miRNA function due to the myriad different cell types, numerous functionally distinct regions, and fluidly dynamic connections between them. This review aims to summarize current understanding of miRNA regulation in neurodevelopment, beginning with miRNAs that establish a general neural fate in cells. Particular attention is given to miR-124, the most abundant brain-specific miRNA, along with its key regulators and targets as an example of the potentially far-reaching effects of miRNAs. These modulators and mediators enable miRNAs to subtly calibrate cellular proliferation and differentiation. To better understand their mechanisms of action, miRNA profiles in distinct populations and regions of cells have been examined as well as miRNAs that regulate proliferation of stem cells, a process marked by dramatic morphological shifts in response to temporally subtle and refined shifts in gene expression. To tease out the complex interactions of miRNAs and stem cells more accurately, future studies will require more sensitive methods of assessing miRNA expression and more rigorous models of miRNA pathways. Thorough characterization of similarities and differences in specific miRNAs’ effects in different species is vital to developing better disease models and therapeutics using miRNAs.